Investigation and analysis of fatal accidents reporting practices in the Punjab province of Pakistan and remedial measures. (October 2021) - Ur Rehman, Atta; Emad, Muhammad Zaka; Khan, Muhammad Usman; Saleem, Muhammad Ahsan; Saki, Saqib A.
Abstract: Mining is one of the most hazardous industries as mineworkers are exposed to unsafe working conditions. One of the key steps in improving mine safety is through study and analysis of mine accident data. In recent years researchers have rigorously worked towards the analysis of mine accidents in Pakistan, but very little work if none is conducted to investigate and analyze the mine accidents reporting system in Pakistan. This research focuses towards analyzing the occurrence of surface mining accidents in Punjab from year 2004–2018 during which 377 fatalities occurred. Intensive literature review is done to understand the current body of knowledge in mine accidents in Pakistan. This work identifies that mining fatalities are increasing with each year unlike global trends with a pattern of consistent occurrence due to primitive mining practices, negligence of workers, lack of resources, slackness on part of regulatory bodies and mine management and worse accident reporting mechanism. The work finds that only fatal accidents or extremely serious accidents are reported to regulatory body. The work identifies the limitations of accident reporting tool (Form IX) as being outdated and generic that abstains from binding cause of accident to any of the stakeholder to be held accountable along with no centralized system to investigate indigenous solutions for improving safety. This work presents a new accident reporting tool that will help improving the overall safety of mining activity by binding occurrence of accidents with responsible stake holders. The approach to make stake holders accountable will result in overall ownership of mine safety in the Pakistan. The future work can investigate the proposed work and quantify the outcomes resulting from the opting the proposed system. Highlights: Majority of fatalities in surface mining operation in Punjab are occurring in Sargodha. Most of the fatalities occur at sandstone surface mining operation in Punjab. Accident reporting form is generic and does not help in future remediation of accident. Young workers are more prone to fatal accidents than old workers. Majority of accidents occur due to bad mining practices or improper PPEs.